Epstein-Barr virus (EBV) status in colorectal cancer: a mini review. Issue 3 (4th March 2019) - Bedri, Shahinaz; Sultan, Ali A.; Alkhalaf, Moussa; Al Moustafa, Ala-Eddin; Vranic, Semir
ABSTRACT: Epstein-Barr virus (EBV) is a well-characterized oncovirus, associated with several malignancies. The complex and heterogeneous nature of colorectal cancer (CRC) has led to many epidemiological causal associations with CRC. However, a direct causal link between microbial infections and CRC has not been established yet. Our review indicates that the current evidence for the presence and role in EBV in CRC is insufficient and contradictory. The design of the analyzed studies, sample size as well as methodology used for EBV detection varied markedly and consequently may not lead to meaningful conclusions. The presence of EBV in other colorectal tumors (lymphomas, smooth muscle tumors) is in line with their status at other anatomic locations and may have therapeutic implications with EBV-specific vaccines. On the other hand, studies exploring EBV in colorectal adenoma-carcinoma sequence and its molecular genetic characteristics are largely missing and may significantly contribute to a better understanding of the role of EBV in CRC.